2021
DOI: 10.1007/s10557-021-07252-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil Ameliorates Doxorubicin-Induced Cardiotoxicity in Rats, as Evaluated by 7 T Cardiovascular Magnetic Resonance Imaging

Abstract: Purpose Doxorubicin-induced cardiotoxicity (DIC) is a common side effect of doxorubicin chemotherapy, and a major mechanism of DIC is inflammation. However, no effective method exists to prevent DIC. In the present study, we investigated the cardioprotective effects of nicorandil against DIC using multiparametric cardiac magnetic resonance (CMR) imaging and elucidated the anti-inflammatory properties of nicorandil in rat models. Methods Male Sprague-Dawley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The resulting stream was connected to a sample vial to collect the nal mixture. The main products were separated by silica gel chromatography and were conrmed by 1 H NMR, 13 C NMR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting stream was connected to a sample vial to collect the nal mixture. The main products were separated by silica gel chromatography and were conrmed by 1 H NMR, 13 C NMR.…”
Section: Methodsmentioning
confidence: 99%
“…9 Along with an increasing focus on the utilization of natural resources in organic synthesis, nicotinamide derivatives are gaining more and more interest. Numerous nicotinamide derivatives with various substituents have been applied to medicine and agrochemistry, such as AAT-008 (EP4 receptor antagonists), 10 boscalid and diflufenican (broad-spectrum fungicide), 11 nicorandil (cardiovascular medicines), 12,13 coramine (respiratory stimulant), apatinib (anti-cancer) 14,15 ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diazoxide inhibited creatine kinase and LDH release from H9c2 cells, mitochondrial permeability transition pore (MPT pore) opening, Ca 2+ overload, ROS generation, and apoptosis [126]. It was found that nicorandil and diazoxide prevented doxorubicin‐induced cardiofibrosis and apoptosis in rats [99].…”
Section: Katp Channels and Apoptosismentioning
confidence: 99%